COUPLING AGENT EFFECT ON THE TENSILE STRENGTH PROPERTIES OF SISAL FIBER-PLASTIC COMPOSITES - Prabawa, Sigit Baktya (Indonesian Journal of Forestry Research, 2005)
The fiber-plastic composites were made from the compounding of plastic (polypropylene) and sisal  (Agave sisalana)fiber with or without  addition of coupling agent (Maleic anhydride grafted polypropylene).  The tensile  strength (Modulus of Elasticity-MOE, Modulus of Rupture-MOR) of the composites were evaluated in the three different conditions, i.e. air dry condition (control), 24 - hour immersion in cold water and 2-hour immersion  in boilingwater.  The results showed that the addition of coupling agent enhanced the properties of the composites.   These properties did not significantly change although  the composites  were immersed in cold water as long as 24 hours.    However, immersion in boiling water for 2 hours, tended to decrease MOR and MOE of the composites.